Bronchoscopic Balloon Dilatation for Tuberculosis-related Bronchial Stenosis: A Rare Case - Wahyuni, Titis Dewi; Alatas, Mohamad Fahmi; Widysanto, Allen; Siahaan, Sylvia Sagita; Muljadi, Rusli; Carolline, Chaifung (Respiratory Science, 2024)
Background: Bronchial stenosis is known as a complication of endobronchial tuberculosis (EBTB). The incidence of stenosis affects quality of life. A minimally invasive therapeutic strategy, bronchoscopic balloon dilatation (BBD), can be chosen to manage the disease. Case: A 29-year-old woman suffered from bronchial stenosis, which appeared after completing treatment for tuberculosis (TB). She was diagnosed with TB around the middle of her pregnancy. She received anti-tuberculosis treatment for six months. Two years later, she complained of a persistent cough for two weeks prior to hospitalization. A complete stenosis of the left main bronchus with atelectatic on the left lung was seen on a chest CT scan. The result was confirmed with a bronchoscopy procedure. There were no mycobacteria or other suspicious organisms found in bronchial washings. Bronchoscopic balloon dilatation action was successful. Discussion: Endobronchial tuberculosis is a tuberculous infection that affects the tracheobronchial tree. It can be treated with minimally invasive procedures like bronchoscopy or surgical interventions. If the stenosis is mild or moderate, several procedures such as balloon dilatation, stents, laser photoresection, argon plasma coagulation, and cryotherapy are often performed. Bronchoscopy balloon dilatation nowadays has become a more preferred treatment option for tracheal and bronchial stenosis because  it may be areliable and effective method.    Conclusion: The BDD procedure in this patient showed good results. This procedure is fast, easy, safe, minimally invasive, and the symptoms resolve quickly. It can be concluded that BBD is a safe and effective therapy for TB-related bronchial stenosis, but the long-term effects of the procedure remain to be monitored.